Formula used : By the virtue of similarity, if any two angles of the triangles are congruent, the third one will also be congruent

Proof : In triangles JOG and MHG,

\(\displaystyle\angle{G}\) is common angle

\(\displaystyle\vec{{{M}{J}}}\stackrel{\sim}{=}\vec{{{G}{J}}}\) (Rhombus)

\(\displaystyle\angle{J}{O}{G}=\angle{M}{H}{G}={90}^{{\circ}}\)

Thus, using virtue of similarity, we know that triangles JOG ang MHG are similar triangles.

Now,

\(\displaystyle\angle{G}\) is common angle

Thus, we know that

\(\displaystyle\triangle{J}{O}{G}\stackrel{\sim}{=}\triangle{M}{H}{G}\)

Hence, by virtue of congruency, \(\displaystyle\vec{{{M}{H}}}\stackrel{\sim}{=}\vec{{{J}{O}}}\)

Proof : In triangles JOG and MHG,

\(\displaystyle\angle{G}\) is common angle

\(\displaystyle\vec{{{M}{J}}}\stackrel{\sim}{=}\vec{{{G}{J}}}\) (Rhombus)

\(\displaystyle\angle{J}{O}{G}=\angle{M}{H}{G}={90}^{{\circ}}\)

Thus, using virtue of similarity, we know that triangles JOG ang MHG are similar triangles.

Now,

\(\displaystyle\angle{G}\) is common angle

Thus, we know that

\(\displaystyle\triangle{J}{O}{G}\stackrel{\sim}{=}\triangle{M}{H}{G}\)

Hence, by virtue of congruency, \(\displaystyle\vec{{{M}{H}}}\stackrel{\sim}{=}\vec{{{J}{O}}}\)